Organic traffic control - Prothmann, Holger (KIT Scientific Publishing, 2011)
Modern cities cannot be imagined without traffic lights controlling the road network. To handle the network's changing demands efficiently, the signal plan specification needs to be shifted from the design time to the run-time of a signal system. The generic observer/controller architecture proposed for Organic Computing facilitates this shift. A two-levelled learning mechanism optimises signal plans on-line while a distributed coordination mechanism establishes green waves in the road network.